Writing out the storm trauma and the work of composition - Rogers, Scott L. (2011)
The discourses of "trauma" and "post-trauma" have become pervasive in representations of life as it is lived in contemporary globalized culture. As new media technologies make the world more accessible, we become accustomed to overwhelming social, political, and personal circumstances, and we come to see "trauma" everywhere, all the time. My dissertation project responds to the presence of "trauma" in the writing classroom, as it appears purposefully in pedagogies designed to respond to it, and as it appears naturally through the interests and experiences of students and teachers who come into contact with national, natural, or personal disaster. Specifically, I question how ideas about "trauma" and "post-trauma" circulate in composition and rhetoric studies from other disciplinary sites like psychology, history, and trauma studies, as well as how these ideas are changed when invoked by composition and rhetorical scholarship.